Gaya Bahasa dalam Diksi “Malam” pada Kumpulan Puisi karya Chairil Anwar - Ronaldo; Muhammad Adek (Persona: Kajian Bahasa dan Sastra, 2023)
The poet Chairil Anwar often uses the word "night" in his poems. The choice of this word certainly has a specific purpose and agenda. The purpose of this study is to describe the form of figurative language and the function of figurative language that contains the word "night" in Chairil Anwar's poems. This type of research is literary research with descriptive methods. Descriptive research method is a method that is described in words or pictures, not in the form of numbers. The data source for this study is a collection of poems by Chairil Anwar which are found in three books, namely The Roar of Mixed Dust (1949), Sharp Pebbles That Are Snatched and Broken (1949), and Tiga Revealed Destiny (1950). Data collection techniques in this study were carried out by steps; reading and understanding a poem by Chairil Anwar which uses the word “night”; mark the data that are in accordance with the research problem found in Chairil Anwar's poems; inventory data. Data analysis techniques consist of data classification, data description and interpretation, and drawing conclusions. The results of this study indicate that the diction "night" in Chairil Anwar's poetry contains a figurative language of affirmation, comparison, satire; As for the functions contained in the word malam in the poem by Chairil Anwar, they include aesthetic functions, ethical functions, and reflective functions.